Efficacy and safety of combinations of mirabegron and solifenacin compared with monotherapy and placebo in patients with overactive bladder (SYNERGY study). (8th June 2017) - Herschorn, Sender; Chapple, Christopher R.; Abrams, Paul; Arlandis, Salvador; Mitcheson, David; Lee, Kyu‐Sung; Ridder, Arwin; Stoelzel, Matthias; Paireddy, Asha; van Maanen, Rob; Robinson, Dudley
Abstract : Objective: To evaluate the potential of solifenacin 5 mg combined with mirabegron 25 or 50 mg to deliver superior efficacy compared with monotherapy, with acceptable tolerability, in the general overactive bladder (OAB) population with urinary incontinence (UI). Patients and Methods: After a 4‐week placebo run‐in, patients aged ≥18 years with wet OAB (urgency, urinary frequency and UI) for ≥3 months who recorded on average ≥8 micturitions/24 h, ≥1 urgency episode/24 h, and ≥3 UI episodes over the 7‐day micturition diary, were eligible for randomisation to double‐blind treatment [2:2:1:1:1:1 ratio, solifenacin 5 mg + mirabegron 25 mg (combined S5 + M25 group); solifenacin 5 mg + mirabegron 50 mg (combined S5 + M50 group); solifenacin 5 mg; mirabegron 25 mg; mirabegron 50 mg; or placebo for 12 weeks], and 2‐weeks' single‐blind, placebo run‐out. Co‐primary efficacy variables were change from baseline to end of treatment (EoT) in the mean number of UI episodes/24 h and micturitions/24 h, assessed using a 7‐day electronic micturition diary. Secondary efficacy variables included change from baseline to EoT in the mean volume voided/micturition, change from baseline at weeks 4, 8, 12 and EoT in mean number of UI episodes/24 h, micturitions/24 h, urgency episodes/24 h, urgency UI (UUI) episodes/24 h and nocturia episodes/24 h; the percentage of patients (responders) achieving zero UI episodes/24 h at EoT in the last 7 days prior to each visit, micturition frequency normalisation (<8 episodes/24 h) at weeks 4, 8, 12 and EoT; and the number of UUI episodes and nocturia episodes in the 7‐day diary. Safety assessments included incidence and frequency of treatment‐emergent adverse events (TEAEs), post‐void residual (PVR) urine volume, and changes from baseline in laboratory parameters. Results: Whilst the combined S5 + M50 group was superior to solifenacin 5 mg for UI, with a mean (standard error) adjusted difference of −0.20 (0.12) UI episodes/24 h (95% confidence interval −0.44, 0.04, P = 0.033), there was no statistical superiority vs mirabegron 50 mg [−0.23 (0.12) UI episodes/24 h; P = 0.052]. In secondary analyses, all active treatment groups had greater improvements in UI episodes/24 h vs placebo, with effect sizes for the combined therapy groups (combined S5 + M25 group: −0.70 episodes/24 h; combined S5 + M50 group: −0.65 episodes/24 h) that were substantially higher than those obtained with monotherapy (range −0.37 episodes/24 h for mirabegron 25 mg to −0.45 episodes/24 h for solifenacin 5 mg). For micturitions/24 h, adjusted change from baseline to EoT was greater in the combined therapy groups vs monotherapies (combined S5 + M50 group, nominal P values 0.006 and <0.001 vs solifenacin 5 mg and mirabegron 50 mg, respectively; combined S5 + M25 group, nominal P values 0.040 and 0.001 vs solifenacin 5 mg and mirabegron 25 mg, respectively). All active treatment groups had greater improvements in the mean numbers of micturitions/24 h vs placebo, with effect sizes for the combined therapy groups (combined S5 + M25 group: −0.85 micturitions/24 h; combined S5 + M50 group: −0.95 micturitions/24 h) higher than with mirabegron monotherapy (25 mg: −0.36; 50 mg: −0.39 micturitions/24 h) and solifenacin 5 mg (−0.56 micturitions/24 h). The combined S5 + M50 group was statistically significantly superior to both monotherapies at EoT for UUI episodes, urgency episodes and nocturia, with effect sizes that appeared to be additive. The combined S5 + M25 group was statistically significantly superior to mirabegron 25 mg for the same variables, except for nocturia. In responder analyses at the EoT, odds ratios in favour of both combined therapies vs monotherapies were shown for the proportion of patients with zero UI episodes and those achieving micturition frequency normalisation. There was a slightly increased frequency of TEAEs in the combined therapy groups vs monotherapies and placebo. Most of the TEAEs were mild or moderate in severity. Events indicative of urinary retention were reported slightly more frequently in the combined therapy groups vs monotherapy and placebo. PVR volume was slightly increased in the combined therapy groups vs solifenacin 5 mg, mirabegron monotherapy, and placebo groups. There were slightly higher frequencies of dry mouth, constipation, and dyspepsia in the combined therapy groups vs monotherapies. There were no concerns regarding electrocardiograms and laboratory data. Conclusion: In the largest OAB study to date, combined therapy with solifenacin 5 mg + mirabegron 25 mg and solifenacin 5 mg + mirabegron 50 mg provided consistent improvements in efficacy compared with the respective monotherapies across most of the outcome parameters, with effect sizes generally consistent with an additive effect. Although the combined S5 + M50 group did not achieve a statistically significant effect vs mirabegron 50 mg in the primary analysis of one of the co‐primary endpoints (change from baseline in mean number of UI episodes/24 h), it approached statistical significance ( P = 0.052), and the nominal P values for the other co‐primary endpoint (micturitions/24 h) were <0.05. Most effects of combined therapy vs monotherapy were observable by week 4. The clinical relevance of the improvements seen with combined therapy for several objective OAB outcome measures was also supported by the improvements of combined therapy vs monotherapy in the responder analyses.